2009
DOI: 10.1007/978-3-642-02008-7_31
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between DNA Periodicity and Local Chromatin Structure

Abstract: Abstract. DNA periodicity and its relationship to the formation of nucleosomes has been investigated extensively using autocorrelation and Fourier transform methods. We provide a precise treatment of the mathematical foundation for this type of analysis, and we apply the resulting method to quantify dinucleotide periodicity in several datasets. We begin by demonstrating, via simulation, the sensitivity of our method relative to previous methods. We then provide evidence of pervasive ∼10 bp periodicity in S. ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…By contrast, both DAC and DCC functions in mouse and human genes exhibit no recognizable peaks and SS patterns are missing in mammals, consistent with earlier studies (Tolstorukov et al 2009;Reynolds et al 2009). This lack of sequence periodicity in mammals is remarkable because it suggests that the enrichment of anti-WW/SS nucleosomes is not due to intrinsic DNA sequence patterns but to trans-acting factors such as RNA Pol II.…”
Section: Periodic Dna Patterns Are Missing In Mammalian Genessupporting
confidence: 90%
“…By contrast, both DAC and DCC functions in mouse and human genes exhibit no recognizable peaks and SS patterns are missing in mammals, consistent with earlier studies (Tolstorukov et al 2009;Reynolds et al 2009). This lack of sequence periodicity in mammals is remarkable because it suggests that the enrichment of anti-WW/SS nucleosomes is not due to intrinsic DNA sequence patterns but to trans-acting factors such as RNA Pol II.…”
Section: Periodic Dna Patterns Are Missing In Mammalian Genessupporting
confidence: 90%
“…First, the NPS software uses a bin size of 10 nucleotides in processing the short-read sequencing data and estimating the dyad positions, resulting in an average error of at least 5 nucleotides in each position estimate which would smooth out any 10 bp periodicity in the average pattern. Second, 10 bp periodicity of the AA dinucleotide has to date been observed only in small sets of H. sapiens nucleosomal sequences and is not observable on a genome-wide scale in H. sapiens , in sharp contrast to S. cerevisiae [12], [27]. While removing the binning step in the NPS process may yield more accurate dyad positions, we caution that it may also amplify the impact of the MNase sequence specificity as is apparent in the higher-resolution yeast data set discussed below.…”
Section: Resultsmentioning
confidence: 97%
“…A commonly cited nucleosome affinity feature is a 10 bp periodicity of certain dinucleotides, which was first described by Trifonov et al in 1980 [5] and has since been confirmed in both synthetic [6], [7] and natural sequences from a variety of organisms including chicken [8], mouse [7], S. cerevisiae [4], [9], [10], worm [10], [11], and H. sapiens [12]. The periodic repetition of these sequence elements, with a period that matches the pitch of the DNA helix, is thought to encourage the large-scale bending of the DNA molecule necessary to form a nucleosome.…”
Section: Introductionmentioning
confidence: 91%
“…Together, the fact that a periodic signal in the region following the TSS can only be measured using either sensitive autocorrelation measures on individual sequences [ 24 ] or the average dinucleotide frequencies of a large set of sequences (this study) suggests that, in contrast to yeast, the RR/YY dinucleotides in human show only a weak periodicity at the level of individual sequences. We thus resolved to use large sets of sequences by partitioning the TSSs into classes according to properties conventionally used to describe genes and to examine if the signal concentrates in a subset of promoters.…”
Section: Resultsmentioning
confidence: 95%
“…This lack of significant periodic dinucleotide patterns in individual human H2A.Z sequences has been noted previously using autocorrelation analysis, in contrast to yeast nucleosomal sequences, where periodic patterns appear readily [ 8 ] using these approaches. However, a more sensitive autocorrelation analysis, called autocorrelation spectral estimation, recently showed that 10- and 11-bp periodic AA/TT dinucleotide signals exist in human nucleosomal sequences, while the 11-bp signal is specific to the regions flanking the TSS [ 24 ].…”
Section: Resultsmentioning
confidence: 99%